Synthesis and Optical Properties of Ho3+, Pr3+ Co-doped LaF3 Nanocrystals - Ha, Hoang Manh; Hoa, Tran Thi Quynh; Van Vu, Le; Long, Nguyen Ngoc (VNU Journal of Science: Mathematics - Physics, 2016)
Abstract: Ho 3+ , Pr 3+  co-doped LaF 3 nanocrystals have been prepared by hydrothermal method. The nanocrystals possess hexagonal structure with   space group with lattice parameters a = 7.17 ± 0.01 Å and c = 7.33 ± 0.01 Å. The room temperature absorption, photoluminescence (PL) and photoluminescence excitation (PLE) spectra of LaF 3 :Ho 3+ , Pr 3+  were investigated in detail. It was discovered that the PL and PLE of Ho 3+ and Pr 3+ ions resulted from the optical intra-configurational f-f transitions. The PL spectra are attributed to the transitions 5 F 3 , 5 S 2 + 5 F 4 and 5 F 5 → 5 I 8 in Ho 3+ ion and the transitions 3 P 0 → 3 H 5 , 1 D 2 → 3 H 4 , 3 P 0 → 3 H 6 , 3 F 2 and 3 F 4 in Pr 3+ ion. The optical transitions 5 I 8 → 5 F 5 , 5 F 4 , 5 F 3 , 3 K 8 , 5 F 1 , 5 G 5 , 3 K 7 and 3 H 6 in Ho 3+ ion and the optical transitions 3 H 4 → 3 P 2 , 3 P 1 , 3 P 0 and 1 D 2 in Pr 3+ ion have been clearly observed not only in the PLE spectra, but also in the absorption spectra. Keywords: LaF 3 :Ho 3+ , Pr 3+ nanocrystals, rare-earth, hydrothermal, absorption, photoluminescence.